2007
DOI: 10.3324/haematol.10820
|View full text |Cite
|
Sign up to set email alerts
|

Use of bortezomib in the management of chronic graft-versus-host disease among multiple myeloma patients relapsing after allogeneic transplantation

Abstract: We report on the use of bortezomib for the management of chronic graft versus host disease (cGVHD) among 8 multiple myeloma (MM) patients who relapsed after reduced-intensity conditioning (RIC) allogeneic transplantation. Five patients (62%) responded to bortezomib demonstrating anti-myeloma effect. Four patients had active cGVHD, including 3 patients with severe punctate keratopathy, at the time of bortezomib administration. All showed an improvement in their condition. This is the first report showing that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
(7 reference statements)
1
14
0
Order By: Relevance
“…12 These data also suggest a higher efficacy of lenalidomide in comparison to thalidomide (ORR 29%) 6 and at least a comparable efficacy to that of bortezomib (ORR 61-73%). [16][17][18] With a median follow up of 16.3 months, the median PFS was 18 months and the median OS was 30.5 months; results that appear superior to those reported with thalidomide (median OS of 12 months) 6 and bortezomib (median PFS of 6 months) 16,17 within comparable settings. In our cohort, the only significant factor influencing PFS and OS was abnormal cytogenetics.…”
Section: Discussionmentioning
confidence: 63%
“…12 These data also suggest a higher efficacy of lenalidomide in comparison to thalidomide (ORR 29%) 6 and at least a comparable efficacy to that of bortezomib (ORR 61-73%). [16][17][18] With a median follow up of 16.3 months, the median PFS was 18 months and the median OS was 30.5 months; results that appear superior to those reported with thalidomide (median OS of 12 months) 6 and bortezomib (median PFS of 6 months) 16,17 within comparable settings. In our cohort, the only significant factor influencing PFS and OS was abnormal cytogenetics.…”
Section: Discussionmentioning
confidence: 63%
“…32 In animal models of GVHD, Bortezomib administration has been shown to prevent GVHD, 9,10 although in neither study were its effects on APC numbers and function tested. In addition, in a recent small study 33 Bortezomib has shown some efficacy in the management of chronic GVHD. However, no data have been reported as yet on monocyte and DC numbers in the peripheral blood or tissues of patients receiving Bortezomib in this as well as other studies.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports, however, on the efficacy of bortezomib in the treatment of chronic graft-versus-host disease (66,67). In animal models, inhibition of TGF-b1 signaling has been shown to decrease the severity of chronic graft-versus-host disease and the severity of bronchiolitis obliterans after allogeneic hematopoietic stem cell transplant (24,68).…”
Section: Therapeutic Proteasomal Inhibitionmentioning
confidence: 99%